Familial Tuberculosis Mimicking Advanced Ovarian Cancer - Fakhrolmolouk Yassaee; Farah Farzaneh (Hindawi Limited, 2009)
Genital TB may present as on abdominopelvic mass mimicking ovarian malignancy because clinical and laboratory findings are similar. Family history is very important and should be considered for differential diagnosis. Three cases of genital TB with presentation of abdominopelvic masses and with no signs and symptoms of TB were presented. Two of them had positive family history of pulmonary TB. Tissue diagnosis was the best method for diagnosis of genital TB, but it should be reminded that if positive family history of TB was present, mini laparotomy should be done to take biopsy and to make rapid diagnosis before treatment.